2018
DOI: 10.1051/matecconf/201823602010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Transport on the Indonesian Economy

Abstract: This study aims to analyze the causal relationship between air transportation and economic growth in Indonesia. The data used are annual time series data from 1990 to 2017 obtained from World Bank. Data analysis method used is method of Vector Error Corection Model (VECM). The results show that there is a relationship between air transport tax and economic growth in Indonesia. Where is the tax of air transport (passenger and goods) and economic growth (GDP). Based on the granger variable or passenger variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This statistical breakdown of the other economic sectors allows for a comprehensive analysis of the impacts of air transport on the economy [2]. Although several economic and econometric approaches can be employed to assess the effects of the air transport sector on the economy, the IO model is an approach that quantifies the direct, indirect, and induced impacts of air transport on the national economy [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This statistical breakdown of the other economic sectors allows for a comprehensive analysis of the impacts of air transport on the economy [2]. Although several economic and econometric approaches can be employed to assess the effects of the air transport sector on the economy, the IO model is an approach that quantifies the direct, indirect, and induced impacts of air transport on the national economy [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nasution et al [11] identified a relationship between air transport and economic growth in Indonesia, connecting the data on passenger/air cargo movement and GDP. One of the main factors related to the GDP growth of a given region may be associated with the investment or expansion of the airport for passengers or its air cargo capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As already stated that the decision to use certain modes are greatly influenced by factors according to the characteristics of road users, for example: availability or ownership private vehicles, driving license, income and the necessity to use modes to work or to deliver children to school [1,3]. In addition to the influence of these factors, the election was also determined influenced by other factors, namely travel time, transportation costs, space availability and the amount of parking fees, comfort and safety, so that the choice of transportation mode is very important in transportation planning [2][3][4].…”
Section: Select Of Mode Transportationmentioning
confidence: 99%
“…The presence of the airport is also considered important to streamline smooth activities of Indonesian citizens who resides in island nations. The role of airport towards economic development is found positive as aviation contributes to direct and indirect impacts to the economic and increase the cycles of economic activities (Darmawan, 2012;Grančay, 2009;Nasution, Azmi, Siregar, & Erlina, 2018;Nurqamarani, 2018).…”
Section: Introductionmentioning
confidence: 99%